2020
DOI: 10.1177/1753193420919060
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage and extensor tendon defects after headless compression screw fixation of phalangeal and metacarpal fractures

Abstract: Osteosynthesis of metacarpal and phalangeal fractures with headless compression screws leads to a defect in the articular surface and possibly damage to the extensor tendons. This study aimed to quantify the articular surface defect and extensor tendon injuries after implant placement in cadaveric hands. Defect size was assessed with computed tomography. Extensor tendon injuries were assessed by direct visualization and measurement after dissection. In the middle phalanx, the defect size in relation to the joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
1
12
1
Order By: Relevance
“…Theoretically, this could jeopardize the extensor central slip at the proximal interphalangeal joint (Nucci et al., 2018). However, this is not supported by clinical and experimental data, as suggested by the absence of secondary boutonnière deformity in our series and by the results of the cadaveric study of Urbanschitz et al. (2020).…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Theoretically, this could jeopardize the extensor central slip at the proximal interphalangeal joint (Nucci et al., 2018). However, this is not supported by clinical and experimental data, as suggested by the absence of secondary boutonnière deformity in our series and by the results of the cadaveric study of Urbanschitz et al. (2020).…”
Section: Discussioncontrasting
confidence: 95%
“…Obviously, this technique implies some damage to the articular cartilage from passage of the screw. Some cadaveric studies have quantified cartilage disruption relative to the entire articular surface, but the clinical relevance of these findings is still unknown (Borbas et al., 2016; Urbanschitz et al., 2020). In our study no radiographical signs of articular degeneration were found at final follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urbanschitz et al demonstrated an avoidance of extensor tendon injury with open technique when compared with percutaneous in both metacarpal and phalangeal fractures. 29 Upon dissection analysis of tendon, there was significantly less damage in the open technique ( P < 0.001) due to direct tendon visualization and protection. The authors also found a higher incidence of tendon injury in fixating phalanges compared with metacarpal regardless of anterograde or retrograde percutaneous technique.…”
Section: Pearls and Pitfallsmentioning
confidence: 95%
“…Considerations can be given to a true percutaneous technique when taking into consideration the potential for injury to the extensor mechanism. Urbanschitz, et al demonstrated an avoidance of extensor tendon injury with open technique when compared to percutaneous in both metacarpal and phalangeal fractures [28]. Upon dissection analysis of tendon, there was significant less damage in open technique (p < 0.001) due to direct tendon visualization and protection.…”
Section: Percutaneous Placementmentioning
confidence: 99%